Job satisfaction among doctors of a tertiary care hospital of eastern India (Nepal Journal of Epidemiology, 2016)
Background: Job satisfaction expresses the extent of congruence between an individual’s expectation of the job and the reward that the job provides. Job satisfaction among doctors is an issue that is of utmost importance because of factors like patient relationships and time pressures associated with managed care. The current study was done to determine the level of job satisfaction in doctors posted in a tertiary care hospital of eastern India and to find out the factors associated with it.Materials and Methods: A descriptive cross sectional study was conducted among 255 doctors posted in a tertiary care hospital of eastern India. Data were collected using a self-reported questionnaire consisting of 49 items addressing the seven domains of job satisfaction, where higher values indicated higher level of satisfaction. The average scores of items were computed to construct factor scores for each individual. Two stage cluster analysis was performed to get the proportion of satisfied doctors and binary logistic regression was used for comparison of predictors of job satisfaction.Results: The proportion of job satisfaction was found to be 59.6% and the most important factor was found to be working space. On adjustment, the odds of being satisfied were found to be higher in the older age groups, among males, doctors posted in preclinical or paraclinical departments and those staying in present setting for 5 years or more.Conclusion: More than half of the doctors were found to be satisfied with their job which can help the policy makers to make necessary strategies to increase the level of satisfaction of the employees.